Content analysis of macro- and micro-elements in water from Belgrade plumbing: Purified in Bežanija treatment plant: During the period of 2008-2015 - Miloš B. Rajković; Mirjana Stojanović; Gordana Pantelić; Savković Maja Eremić (Zaštita Materijala)
An indirect method of metal content determination in drinking water based on a study of scale, showed precision, reliability and reproducibility of the obtained results. Results showed that the water quality, based on the metal content in the water, is quite constant and metals are in a concentration allowed by the Regulations. An increase of Uranium in drinking water (mainly the isotope 238U) was determined and its anthropogenic origin is proven based on the results of fractional extraction. Based on the content of macro- and microelements it is determined type of tested water as HCO3- Ca-Mg. In the examined period the concentration of macro- and microelements was below the MAC (Maximum Allowable Concentration) values. Ratio of Ca/Mg according to the Regulations should be between 3 and 4, while in the period of examination was varied in the range of 10.67 to 16.76, which means that the content of Mg in water is very low. Regarding to the period of 2011-2015 the input of heavy metals via drinking water was significantly increased (even 10 times) in comparison to the period of 2008-2011. As result of increased concentrations of Fe and Zn is a high growth of heavy metals. Calculated data showed that the risk of input microelements: Al, Fe and Pb, which are in studied water much higher than allowed by the Regulations, is not having any short-term risk to human health. Data analysis of the risk on the long-term health showed that the only real danger is the presence of Pb in drinking water. The risk of cancer is present in 23-58 population of 1000 people who are using this water for drinking.